2016
DOI: 10.1002/cm.21311
|View full text |Cite
|
Sign up to set email alerts
|

Myosin‐10 independently influences mitotic spindle structure and mitotic progression

Abstract: The iconic bipolar structure of the mitotic spindle is of extreme importance to proper spindle function. At best, spindle abnormalities result in a delayed mitosis, while worse outcomes include cell death or disease. Recent work has uncovered an important role for the actin-based motor protein myosin-10 in the regulation of spindle structure and function. Here we examine the contribution of the myosin tail homology 4 (MyTH4) domain of the myosin-10 tail to the protein’s spindle functions. The MyTH4 domain is k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 42 publications
4
27
1
Order By: Relevance
“…Previous reports showed that MYO10 has a direct function in meiotic spindle formation (Sandquist et al 2016, Weber et al 2004, Woolner et al 2008. In contrast to the tubulins, 165 actins, and other spindle proteins that did not appear to be altered in the absence of NEK1, we observed that the levels of the myosins, MYO5, MYO7A, MYO10 and MYO15, were significantly increased in testis protein extracts from Nek1 mutant mice compared to wildtype littermates (Table S1).…”
Section: Lack Of Nek1 Results In Deregulation Of Myosin X (Myo10) Andcontrasting
confidence: 49%
See 1 more Smart Citation
“…Previous reports showed that MYO10 has a direct function in meiotic spindle formation (Sandquist et al 2016, Weber et al 2004, Woolner et al 2008. In contrast to the tubulins, 165 actins, and other spindle proteins that did not appear to be altered in the absence of NEK1, we observed that the levels of the myosins, MYO5, MYO7A, MYO10 and MYO15, were significantly increased in testis protein extracts from Nek1 mutant mice compared to wildtype littermates (Table S1).…”
Section: Lack Of Nek1 Results In Deregulation Of Myosin X (Myo10) Andcontrasting
confidence: 49%
“…To ensure correct spindle dynamics, the spindle assembly checkpoint (SAC) becomes activated in situations where tension is not appropriately established between the chromosomes and the spindle poles, and this will block the progression of the cell cycle to prevent aberrant segregation. In addition to the canonical SAC, other levels of control have been described, including MYO10 (Sandquist et al 2016, Weber et al 2004, Woolner et al 2008. In oocytes and frog embryos, disruption of MYO10 negatively affects nuclear anchoring and meiotic spindle formation (Weber et al 2004), while depletion of MYO10 in frog epithelial cells induces abnormal spindle movements, spindle elongation, multi-spindle and pole fragmentation (Kwon et al 2015, Woolner et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For example, live imaging in Xenopus embryos has revealed how the molecular motors, dynein and myosin‐10, function to maintain spindle bipolarity during mitosis (Jones et al, ; Woolner et al, ). Moreover, Xenopus eggs and embryos have also uncovered how myosin‐10, which can bind to both actin and microtubules, regulates spindle length, orientation and dynamics through interactions with both cytoskeletons (Sandquist, Larson, & Hine, ; Weber, Sokac, Berg, Cheney, Bement, ; Woolner et al, ; Woolner & Papalopulu, ). In related work, live analysis revealed that highly dynamic F‐actin cables are associated with the mitotic spindle as it assembles and proceeds through metaphase and anaphase.…”
Section: Methods For Investigating Mitosis and Cell Division In Xenopusmentioning
confidence: 99%
“…3). Remarkably, at least part of Myo10’s contribution to mitosis is somehow mediated through control of cell cycle progression, as the depletion of Myo10 (Woolner et al, 2008) or expression of its isolated “Myth4” domain (Sandquist, Larson, & Hine, 2016) greatly slows the metaphase–anaphase transition. While it is not yet known how widely required Myo10 is for cell division in other systems, Myo10 has been implicated in spindle formation in Xenopus and mammalian meiosis (Brieño-Enríquez et al, 2017; Weber et al, 2004), and in spindle stability and dynamics in several cultured cell types (Chan, Hsu, Liu, Lai, & Chen, 2014; Iwano et al, 2015; Kwon, Bagonis, Danuser, & Pellman, 2015; Kwon et al, 2008; Toyoshima & Nishida, 2007).…”
Section: Introductionmentioning
confidence: 99%